Evaluation of early functional outcome of arthroscopic decompression in chronic primary sub-acromial impingement syndrome - Pritam Samanta; Rajesh Kumar Chopra; Jatin Prakash; Ashish Jaiman (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2023)
Background: Sub-Acromial Impingement Syndrome (SAIS) spectrum ranges from acute inflammation to chronic degeneration of the bursa and of rotator cuff tendons in sub-acromial space. It may lead to a full-thickness tear of rotator cuff tendons and degenerative joint disease of the shoulder girdle leading to functional loss and disability if not treated early and adequately. This study aimed to determine the early functional outcome of arthroscopic sub-acromial decompression in chronic SAIS due to mechanical causes. Material and methods: This was a prospective cohort study. Patients were operated on arthroscopically for sub-acromial decompression between September 2018 and March 2020. Thirty-five patients with a range of 20 to 65 years of age diagnosed clinically with primary chronic sub-acromial impingement syndrome meeting the inclusion criteria were included in this study. All the patients under study were initially kept for at least four weeks of a course of conservative treatment and persisted in having symptoms were treated surgically with arthroscopic sub-acromial decompression. The UCLA (The University of California at Los Angeles) shoulder rating scale was used to assess shoulder function. The assessment was done in the pre-operative period, four weeks, 12 weeks, and 16 weeks post arthroscopic sub-acromial decompression surgery. Results: Compared to pre-operative UCLA shoulder function score at the end of non-operative conservative treatment, the patients under study showed a statistically significant improvement at the end of the 16th week of post-arthroscopic subacromial decompression (p<0.0001). Conclusion: This study concludes that arthroscopic sub-acromial decompression provides a good functional outcome in patients having primary shoulder impingement due to extrinsic mechanical causes such as shape and slope of the acromion in the absence of significant (total or near total) rotator cuff tear after 16 weeks of follow-up.